Challenges in Criminal Law Enforcement against Political Patronage in Regional Head Elections - Ismayawati, Any; Aristoni, Aristoni; Rosyada, Amrina (De Jure: Jurnal Hukum dan Syari'ah, 2025)
The transition from a representative to a direct election system has opened wider access to political participation, allowing the public to directly elect candidates for governor, regent, and mayor. However, various groups see this system as an opportunity for political patronage, potentially involving money politics, that may undermine integrity and substantive democracy at the local level. This study aims to examine the challenges of enforcing criminal law against political patronage in regional head elections, primarily focusing on exploring the perceptions and behaviour of the Karimunjawa Jepara community towards the practice of political patronage, as well as the challenges and solutions faced by the Integrated Law Enforcement Centre in enforcing criminal law against such practices in regional elections. Furthermore, the findings were analysed using a legal anthropology and siyasah shar'iyyah approach. The results of this study indicate that the people of Karimunjawa remain permissive towards political patronage practices due to their apathy towards candidate pairs and socio-economic conditions. The weakness of evidence, driven by the public's unwillingness to testify, is a crucial challenge for the Integrated Law Enforcement Centre in enforcing criminal law during regional elections. From legal anthropology and siyasah shar'iyyah perspectives, these findings reflect the lack of optimisation in the internalisation of legal and Islamic values in the community's political attitudes. Therefore, a continuous legal outreach program and education that adhere to local values and Islamic spirituality are essential to overcome this problem. This research contributes to integrating electoral criminal law with Islamic values, while serving as a reference for the Integrated Law Enforcement Centre, the Election Supervisory Body, and related parties in formulating fair and progressive legal policies for the enforcement of electoral law.